Dynamics and stability – A proposal for related terms in Metrology from a mathematical point of view. (February 2016) - Ruhm, Karl H.
Highlights: Terms around dynamic systems in Metrology are discussed. Main terms are systematically derived on a mathematical basis. Time dependent properties are assigned to signals and parameters. Abstract: We describe measurement quantities and measurement processes verbally by using everyday terms, often sanctioned by international standards and guides. However, we apply some of these terms inconsistently as compared to definitions in base sciences like Logic and Mathematics, Signal and System Theory, Stochastics and Statistics, Estimation and Optimisation Theory. This is especially true for a group of terms in Metrology, namely for the terms kinetic, static, time dependent, time invariant, stable, stationary, drifting etc., which all populate the general environment of the main term dynamics . The paper explores systematic relations between these and similar terms and discusses the aptitude of their implementation in everyday practice. Cardinal point is the term dynamic, which will be investigated thoroughly. So, derived terms can be defined, incorporated and judged accordingly. For the field of Metrology some new and, maybe, surprising results arise, worth being considered in the near future.